Temporal Monitoring of the Floreana Island Galapagos Giant Tortoise Captive Breeding Program. (29th July 2022) - Gray, Rachel; Fusco, Nicole; Miller, Joshua M; Tapia, Washington; Mariani, Carol; Caccone, Adalgisa; Jensen, Evelyn L
Abstract: Captive breeding programs benefit from genetic analyses that identify relatedness between individuals, assign parentage to offspring, and track levels of genetic diversity. Monitoring these parameters across breeding cycles is critical to the success of a captive breeding program as it allows conservation managers to iteratively evaluate and adjust program structure. However, in practice, genetic tracking of breeding outcomes is rarely conducted. Here, we examined the first three offspring cohorts (2017–2020) of the genetically informed captive breeding program for the Floreana Island Galapagos giant tortoise, Chelonoidis niger . This captive breeding program is unique as the Floreana tortoise has been extinct since the 1800s, but its genome persists, in part, in the form of living hybrids with the extant Volcano Wolf tortoise, C. becki . Breeding over the study period took place at the Galapagos National Park Directorate breeding facility in four corrals, each containing three females and two males. Using 17 microsatellite markers, we were able to assign parentage to 94 of the 98 offspring produced over the study period. We observe that despite the addition of more founders since the pilot breeding program, the effective population size remains low, and changes to the arrangements of breeding corrals may be necessary to encourage more equal reproductive output from the males. This study demonstrates the value of hybrids for species restoration and the importance of continually reassessing the outcomes of captive breeding.